Implementing a Group-based Flipped Classroom Model in EFL Writing Class: Challenges and Benefits - Nurdianingsih, Fitri; Fitriati, Sri Wuli; Astuti, Puji; Rozi, Fahrur (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study investigates the implementation of a group-based flipped classroom model in teaching descriptive and narrative writing, focusing on its challenges and benefits. The research involved 35 students whose writing skills were assessed through pre-tests and post-tests, revealing significant improvements in vocabulary usage, organization, coherence, and grammatical accuracy. Statistical analysis, including paired t-tests, confirmed these enhancements with a large effect size (Cohen’s d > 0.8). The flipped classroom approach fostered active learning through pre-class preparation, in-class group activities, and peer feedback, resulting in higher student engagement and collaboration. Both students and lecturers reported positive perceptions of the model, though challenges such as inconsistent pre-class preparation, technological barriers, and uneven group participation were noted. The findings suggest that while the group-based flipped classroom model effectively enhances writing skills and engagement, its success depends on structured support, institutional resources, and careful instructional design. Recommendations for educators include accountability measures for pre-class work and clear group roles, while institutions are advised to invest in technology and teacher training. Future research should explore long-term effects and adaptability across diverse educational contexts.